Konsep dan Pembaruan Residivisme dalam Hukum Pidana di Indonesia (Concept and Reform of Recidivism in Criminal Law in Indonesia) - Prianter Jaya Hairi (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2018)
The legal arrangement of additional penalty for repetition of crime (recidivism) as stipulated in Indonesian Criminal Code has been considered quite complicated to be executed. The draft of the New Indonesian Penal Code Bill brings changes to the concept of recidivism. This study intends to examine the concept of recidivism in the doctrine, in its current arrangement, in the draft of the New Indonesian Penal Code Bill, and to examine the implications of the concepts’ changing for criminal law enforcement in general. In the discussion it is known that the existing Criminal Code, applied the concept of special recidivism with the intermediate system, that will be transformed into a system of